FEEDING OF TEMULAWAK FLOUR MIXED IN FOOD TO THE HEIGHT VILI CHANGES OF BROILER JEJENUM - Krisna, Gede Ari; Ardana, Ida Bagus Komang; Suastika, Putu (Buletin Veteriner Udayana; Vol. 12 No. 2 August 2020DO - 10.24843/bulvet.2020.v12.i02.p04, 2020)
Broiler has high productivity in chicken meat production. The higher the small intestine villi, much greater the effectiveness of the absorption of food extracts through the small intestine epithelium. Nutrients contained in ginger are curcuminoids, minerals, essential oils, fatty oils, carbohydrates, and proteins. This study aims to determine the differences in changes in the height of broiler jejunum villi due to the administration of Curcuma xanthorrhiza Roxb . In several doses in the feed. Samples of this study were 40 male broilers aged 14 days with an average weight of 420g simultaneously divided into 4 treatments consisting of 10 replications. P0 is broiler as a control without being given curcuma flour and only given feed. P1 is broiler which is given 10 g / kg of curcuma powder by mixing it into the feed. P2 is broiler which is given 20 g / kg of temulawak flour by mixing it into the feed. P3 is broiler which is given 30 g / kg of temulawak flour by mixing it into feed, on the day 35 broilers then necropsied and taken by jejunum organ. The results of the analysis showed that the treatment of P2 and P3 had no significant effect (P>0.05) on the control (P0), but P1 was significantly different (P<0.05) on P0, P2, and P3, in P2 treatment, was not significantly different (P>0.05) with P3. The conclusions of this study indicate that the administration of curcuma flour as much as 10 g / kg of feed, is able to increase the height of jejenal villi in broilers.